Peningkatan Kemampuan Komunikasi Matematis dengan Problem Based Learning Terintegrasi Pembelajaran Berdiferensiasi Berbantuan E-Modul Flipbook - Kusumawardhani, Anisa; Widiyastuti, Erni; Hidayat, Abdul Aziz (Universitas Muria Kudus, 2024)
The purpose of this research was to increase mathematical communication with integrated Problem Based Learning (PBL) differentiated learning with a flipbook e-modules media. The type of research was classroom action research (CAR) which four stages namely planning, acting, observing, reflecting. The research subjects were students in class XI.4 at SMAN 2 Purwokerto. Data collection was analysis to used were written tests, observations and field notes. Data analysis was data analysis of written mathematical communication ability test results and observation in class and learning activities. Based on the findings and discussions can be concluded that learning using the integrated Problem Based Learning (PBL) model differentiated learning assisted by flipbook e-modules media can improve student’s mathematical communication skills of. This can be shown from the results of the mathematical communication ability test in the pre-cycle which had an average of 66, cycle I 73.3 and cycle II 80.5. Besides that, the success of the implementation of learning in class increased in cycle I with an average score percentage of 83.93% and cycle II 89.29% with good success criteria and learning can be said to be successful.